The Validity of Student Worksheets Based on ETHNO-STEM Material on Volume of Rotating Objects - Nayazik, Akhmad (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
This research aims to produce a valid Ethno-STEM-based student worksheet product with a rotating object volume material so that it is suitable for use in learning. Ethno-STEM is an innovation in mathematics learning that combines an ethnomathematical approach with a STEM approach. The research method used is Research and Development (R&D) with a 4-D development model which is modified to 3-D due to limited research time. The development stages are the defining, design, and development stages. In this research, only a product validation test was conducted. The instrument used is a validation sheet to measure the product feasibility. The result of this study indicates that the developed student worksheet product meets the very feasible criteria with an overall average of 87,11 %. This shows that the product of developing an Ethno-STEM-based student worksheet with a rotating object volume is possible and feasible to use in learning mathematics.